Fighting Corruption Post Revision of the Act of the Corruption Eradication Commission - Salma Aulia Farahdina Ariani; Nanik Prasetyoningsih (Media of Law and Sharia, 2022)
At the end of 2019, Law Number 19 of 2019 concerning the Second Amendment to Law Number 30 of 2002 concerning the Corruption Eradication Commission was passed. The revision of the Corruption Eradication Commission Law (KPK Law) has generated polemics and interesting issues to discuss.The author wants to examine the role of the KPK in enforcing the law to eradicating corruption in Indonesia. The author will examine how the role of the KPK is compared to the position of the Attorney General's Office and the Police, and analyze the role of KPK in the KPK Law before and after the revision. This research is a normative-empirical legal research, with statutory approach. The results of this study show that the Police, the Prosecutor's Office and the Corruption Eradication Commission both play a role in law enforcement to eradicate corruption. The difference, the three law enforcement agencies in eradicating corruption lies in their existence in the 1945 Constitution, their role in investigations, handling based on case values, and coordination of handling corruption. As for the existence of Law Number 19 of 2019 there are several amendments in the KPK, (1) position of the KPK as a law enforcement agency in the executive branch, (2) establishment of the KPK Supervisory Board, (3) implementation of the wiretapping function, (4) mechanism for issuing an Investigation Termination Order (SP3) (5) institutional coordination of the KPK with other law enforcement (6) search and seizure mechanism, and (7) KPK staffing system.